Prevalence of Sarcopenia and Its Relationships between Physical Performance and Sarcopenia in Patients with Heart Failure: a Preliminary Cross-Sectional Study - เผ่ากันทะ ศิวพงษ์; ศรีนิล สิริกร; พินิจมั้ง ประพรมพร; วัฒนนานนท์ ขนิษฐา; ยืนยงชัยวัฒน์ กรอนงค์ (Journal of Health Science of Thailand, 2023)
Heart failure is an abnormality in the function of heart. This leads to dyspnea, fatigue, edema at limbs. Patients with heart failure are associated with sarcopenia, which is a major problem with exercise endurance, physical performance, mental health problems and reduce the quality of life. Therefore, this study aimed to explore the prevalence of sarcopenia and the relationship between physical performance and sarcopenia in patients with heart failure. One hundred participants; average age 57 years (ages 35 to 75 years old) both males and females were recruited to the study. Participants were performed the physical performance consisted of handgrips strength, skeletal muscle mass index, gait speed, respiratory muscle strength, and 5-time sit to stand. All data were analyzed by SPSS Statistics program. ANOVA and post hoc test with Bonferroni were performed to compare between sarcopenia, possibility of sarcopenia and no sarcopenia. Spearman rank correlation was used to explore the relationship between sarcopenia and physical performance. This study found the prevalence of sarcopenia was 15.0%, the prevalence of possible sarcopenia was 12.0%. Factors significantly associated with sarcopenia in heart failure were sex, age, body mass index, skeletal muscle mass index, handgrips strength, gait speed, respiratory muscle strength and 5-time sit to stand (p<0.05). In addition, these relationships were also remained after adjusted for age and sex. Therefore, this study found the prevalence of sarcopenia was 15.0%. Advanced age, low skeletal muscle mass index, poor handgrip strength, slow gait speed, reduced inspiratory muscle strength and slower sit-to-stand times were observed in chronic heart failure patients with sarcopenia. In addition, the relationship between sarcopenia and physical performance were observed in patients with heart failure.